CADANGAN PENYELESAIAN PAKAR PENDIDIKAN BERKAITAN PENGAJARAN GURU PENDIDIKAN ISLAM DALAM MENGINTEGRASIKAN KEMAHIRAN BERFIKIR ARAS TINGGI (KBAT) DI SEKOLAH MENENGAH: RECOMMENDATIONS OF EDUCATIONAL EXPERTS ON THE TEACHING OF ISLAMIC EDUCATION TEACHERS IN INTEGRATING HIGHER ORDER THINKING SKILLS (HoTS) IN SECONDARY SCHOOLS - Mohd Zeki, Mohd Zaidi; Mustafa Kamal, Noor Muslieah; Hidayat, Riyan; Mazlan, Nurul Hijja; Moshidi, Nurulaini (Journal of Islamic Educational Research, 2021)
This study aims to deeply elaborate with a focus on planning and implementation which is often a challenge on Islamic Education teachers teaching in integrating Higher Order Thinking Skills (HoTS) by four education experts. All participants were selected based on purposive sampling. Referring to the suitability of the study, the exploration was conducted by implementing a qualitative paradigm using a case study design based on semi-structured interview method and document analysis implemented. The findings of the study show that the proposed problem solving by education experts in relation to problems that occurred in the teaching of Islamic Education teachers in integrating HoTS is the process of information delivery, the competence of education officers and dismantling the curriculum. Based on the overall findings of the study shows, Islamic Education teachers need to be skilled in implementing pedagogy accurately based on the current curriculum guided by comprehensive information aimed at supporting the formation of students holistically.